Family-focused intervention programme to foster adolescent mental health and well-being: protocol for a multicountry cluster randomised factorial trial (FLOURISH Phase 2) - Heather M Foran; Marija Raleva; Nina Heinrichs; Graham Moore; Yulia Shenderovich; Xiang Zhao; Judith Simon; Antonio Piolanti; Viorel Babii; Janina Mueller; Franziska Waller; Dennis Wienand; et al. (BMJ Open)
Introduction Adolescent mental health problems represent a significant global health issue, particularly in low- and middle-income countries, such as the Republic of North Macedonia and the Republic of Moldova. Effective and scalable interventions are urgently needed to address these challenges.Methods and analysis This protocol outlines a multicountry cluster randomised factorial trial, implemented according to the multiphase optimisation strategy (Phase 2), which evaluates the effectiveness and costs of three add-on components for the Parenting for Lifelong Health for Parents and Teens programme: adolescent mental health tools based on UNICEFs Helping Adolescents Thrive comics, adolescent peer support based on UNICEFs ‘I Support My Friends’ intervention and engagement booster designed to enhance attendance and programme completion through incentives. The study will recruit 720 families and involve 64 clusters in North Macedonia and Moldova. Primary outcomes will include adolescent internalising problems and social support, family functioning and attendance during the programme. Secondary outcomes will assess broader aspects of mental health among caregivers and adolescents, as well as implementation and cost outcomes. Data will be collected at baseline and postintervention, approximately, 8 weeks later. Statistical analyses will include regression models to assess the main and interaction effects of the intervention components and cost analyses.Ethics and dissemination The study received ethical approval from the University of Klagenfurt in Austria (approval number: 2023–013), the Medical Faculty at St. Cyril and Methodius University in North Macedonia (approval number: 03-2144/4) and the National Committee of Ethical Expertise for Clinical Trials in Moldova (approval number: 1476). The results will be disseminated through peer-reviewed journals, conferences, webinars in multiple languages, regional forums, stakeholder meetings with policymakers and practitioners, public communication through media engagement and open access platforms, including data sharing and early release of findings.Trial registration details Trial registration: NCT06562244; Project page: https://www.flourish-study.org/about.html